Sub-solutions and mean-value operators for ultraparabolic equations on Lie groups - Cinti, Chiara (MATHEMATICA SCANDINAVICA, 2007)
The aim of this paper is to provide a theory of sub-solutions for a class of hypoelliptic ultraparabolic operators $\mathcal L$, by using mean-value operators on the level sets of the fundamental solution of $\mathcal L$.